Kir-hla genes and maternal infant HIV-1 transmission - Hong, Heather Alanna (My University, 2015)
Natural Killer (NK) cells are an essential part of the immune system capable of controlling several viral infections, including HIV-1. Moreover, several studies have linked specific NK cell receptors, termed killer immunoglobulin-like receptors (KIR), and their human leukocyte antigen (HLA) ligands to favourable clinical outcomes in HIV-1 infected individuals. Recent studies have also highlighted the role of KIR and HLA in modulating the risk of adult HIV-1 transmission and disease progression; however, little is known about the role of KIR and HLA in mother-to-child transmission (MTCT) of HIV-1. Therefore, this thesis specifically explores KIR/HLA-ligand combinations in HIV-1 infected mothers and their infants, as well as the KIR/HLA-ligand relationship between mother and infant, in the context of MTCT of HIV-1. The study of HIV-1 exposed uninfected (EU) infants in comparison with HIV-1 in utero (IU) or intrapartum (IP) infected infants provides important information regarding the correlates of protection and/or susceptibility to HIV-1 acquisition. Moreover, having data on HIV-1 transmitting (TR) and non-transmitting (NT) mothers may also highlight maternal factors that increase or decrease HIV-1 transmission.